2021
DOI: 10.1590/1414-431x2021e11409
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and high neutrophil-to-lymphocyte ratio are prognostic factors in non-metastatic breast cancer patients

Abstract: Obesity has been associated with an increased risk of breast cancer recurrence and death. Some readily available biomarkers associated with systemic inflammation have been receiving attention as potential prognostic indicators in cancer, including neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). This study aimed to explore the correlation between body mass index (BMI) and invasive breast cancer and the association of NLR, PLR, and BMI with breast cancer outcomes. We undertook a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…As to PLR and SII, the univariate analysis, showed that neither PLR nor SII was a potential factor associated with OS for breast cancer in our study. The relationship between NLR, PLR, SII, and breast cancer prognosis is complex: many reports concluded that NLR ( 14 , 40 , 41 ), PLR ( 37 , 42 , 43 ), and SII ( 16 , 44 , 45 ) were independent prognostic factors for breast cancer, but there are also many studies that do not support the conclusion mentioned above ( 46 49 ). This may be related to the selection of the population and the included variables.…”
Section: Discussionmentioning
confidence: 99%
“…As to PLR and SII, the univariate analysis, showed that neither PLR nor SII was a potential factor associated with OS for breast cancer in our study. The relationship between NLR, PLR, SII, and breast cancer prognosis is complex: many reports concluded that NLR ( 14 , 40 , 41 ), PLR ( 37 , 42 , 43 ), and SII ( 16 , 44 , 45 ) were independent prognostic factors for breast cancer, but there are also many studies that do not support the conclusion mentioned above ( 46 49 ). This may be related to the selection of the population and the included variables.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be noted that chemotherapy regimens in these studies differed, which may explain the differences observed in these studies. A potential explanation for the decreased risk of hematologic toxicity in obese patients is the presence of chronic inflammation leading to increased neutrophil counts [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the NLR has been found to be significantly higher in obese individuals than in healthy lean individuals [ 132 , 133 , 134 , 135 ], with a positive correlation to the BMI [ 132 , 135 , 136 , 137 , 138 ]. As expected, the NLR is also associated with higher plasma CRP concentrations [ 111 , 132 , 139 , 140 ].…”
Section: Neutrophils In Obesitymentioning
confidence: 99%
“…The significant association between obesity and a high NLR (higher than 4) was a good predictor of increased breast cancer risk. Patients with a high NLR and a high BMI also had the worst disease-free survival [ 133 , 138 ]. More importantly, NLR values were found to correlate significantly with the degree of abdominal obesity [ 141 , 142 ].…”
Section: Neutrophils In Obesitymentioning
confidence: 99%